The influence of self-efficacy on employee performance with job satisfaction as an intervening variable at PT Wahana Andika Mandiri IT Services department - Sthefanus Widodo; Tan Evan Tandiyono (Digital Innovation : International Journal of Management, 2024)
This research aims to prove and analyze the influence of self-efficacy on employee performance through job satisfaction as an intervening variable for employees of PT Wahana Andika Mandiri IT Services Department. By controlling these 3 factors, it is hoped that it can improve employee performance and improve company performance. The type of research used is quantitative research. This research uses a correlational design which aims to determine the relationship and level of relationship between two or more variables without any attempt to influence these variables so that there is no variable manipulation. The method in this research uses a quantitative method and the respondents in this research are taken from IT employees. Services are 76 employees taken from a total population of 251 employees. Data was collected through a questionnaire and then processed using SPSS 25, to determine the results of the influence of self-efficacy on employee performance with job satisfaction as an intervening variable at PT Wahana Andika Mandiri in the IT Services section. The results of this research show that the significance value is less than 0.05 (0.000<0.05) and the calculated t value is greater than the table (9.231 > 1.666). Based on these results, it is concluded that job satisfaction (Z) has a significant and positive influence on employee performance (Y). Employees who are satisfied with their jobs tend to be more motivated, committed and productive. It is concluded that this research has four hypotheses and three variables where the variable Self-efficay has a significant and positive effect on employee performance, Self-efficacy has a significant and positive effect on job satisfaction, job satisfaction has a significant and positive effect on employee performance, Self-efficacy and employee performance have Simultaneous influence on job satisfaction of PT Wahana Andika Mandiri employees in the IT Services section.